Quality monitoring of resuscitative endovascular balloon occlusion of the aorta using cumulative sum analysis in Korea: a case series - Hyunsik Choi; Joongsuck Kim; Kwanghee Yeo; Ohsang Kwon; Kyounghwan Kim; Wu Seong Kang (Journal of Trauma and Injury)
Purpose Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a state-of-the-art lifesaving procedure. However, due to its high mortality and morbidity, including ischemia and reperfusion injury, well-trained medical staff and effective systems are needed. This study was conducted to investigate the learning curve for REBOA in Korea. Methods To monitor this learning curve, we used cumulative sum (CUSUM) analysis and graphs of mortality and aortic occlusion time within 60, 90, and 120 minutes for consecutive patients. The procedures performed between July 2017 and June 2021 were divided into pre-trauma center (pre-TC; July 2017–February 2020) and TC (February 2020–June 2021) periods. Results REBOA was performed for 31 consecutive patients with trauma. The pre-TC (n=12) and TC (n=19) periods did not differ significantly with regard to Injury Severity Score, age, injury mechanism, initial systolic blood pressure, prehospital cardiopulmonary resuscitation (CPR), or CPR in the emergency department. At the 17th consecutive patient during the TC period, CUSUM failure graphs for mortality and aortic occlusion time exhibited a downward inflection, indicating an improvement in performance. Conclusions The mortality and aortic occlusion time of REBOA improved, and these parameters can be monitored using CUSUM analysis at the hospital level.